Development of a specialized product “Baikal Energy”: Protein-carbohydrate - Kotova Tatyana; Khanturgaev Andrey; Khanturgaeva Natalia; Tsytsykov Vladimir (BIO Web of Conferences)
The article discusses the results of developing a specialized product, the protein-carbohydrate bar “Baikal Energy,” made using wild plant materials of the Baikal natural territory. The study’s objective was to create a technology for producing bars using innovative processing methods, such as microwave processing and CO2 extraction, and testing this technology in industrial production conditions. Standard research methods were used throughout the work, including system analysis, synthesis, experimental techniques, and mathematical modeling. The primary attention is paid to the selection of functional ingredients: pine nut cake, sea buckthorn leaves, berries, and medicinal herbs with a high potential for creating products with detoxing and general tonic effects. The study’s results include the development of recipes for three types of bars with different combinations of functional ingredients, creating a production flow chart using microwave equipment, and successfully testing the products. The technology was tested at NPF BaikalBiotechnology LLC production facilities in Ulan-Ude and introduced into production. The data obtained can be used to create other specialized functional food products that help improve health and detoxify the body.